A-MoS3@CNT nanowire cathode for rechargeable Mg batteries: a pseudocapacitive approach for efficient Mg-storage. Issue 34 (21st August 2019) - Zhang, Yujie; Chen, Dong; Li, Xue; Shen, Jingwei; Chen, Zhongxue; Cao, Shun-an; Li, Ting; Xu, Fei
Abstract : a -MoS3 @CNT nanowire is used as a pseudocapacitive Mg-storage material, which exhibits fast solid-state Mg 2+ ions diffusion kinetics. Abstract : Rechargeable Mg batteries are promising candidates for highly safe large-scale energy storage batteries owing to their low-cost and non-dendritic metallic Mg anode. However, exploration of high-performance cathodes remains a great challenge hindering their development. Herein, a new pseudocapacitive Mg-storage nanowire material ( a -MoS3 @CNT) is constructed with a carbon nanotube (CNT) core and an amorphous MoS3 ( a -MoS3 ) outer layer (15 nm thick). The nanowire cathode exhibits a high reversible capacity of 175 mA h g −1 at 100 mA g −1, a good rate performance of 50 mA h g −1 at 1000 mA g −1, and an outstanding long-term cyclability over 500 cycles. Further investigation of the mechanism demonstrates that the Mg-storage of a -MoS3 @CNT is mainly achieved by the pseudocapacitance of a -MoS3, in which Mg 2+ ions show fast solid-state diffusion kinetics. The present results demonstrate a new approach for efficient Mg-storage using pseudocapacitive materials, and the performance and solid-state Mg 2+ diffusion kinetics could be optimized by delicate morphology tailoring.